Absorptive capacity of demand in sports innovation. Issue 4 (19th May 2018) - Almudi, Isabel; Fatas-Villafranca, Francisco; Potts, Jason; Thomas, Stuart
ABSTRACT: We propose a stylized and tractable neo-Schumpeterian model of sectorial transformations in which demand-side knowledge constraints inhibit innovation diffusion and industrial change, causing structural instability. Evolutionary competition in the model implies that innovation can overshoot the absorptive capacity of demand, leading to a slowdown in sectorial dynamism and even to structural collapse. Closed-form analytical results prove the existence of a unique stationary state in the dynamic model that is (globally) asymptotically stable. We show how the dynamic paths and the stationary rest-point depend on the trade-off between innovation and demand absorptive capacity parameters. To illustrate the plausibility and relevance of our results, we examine the Australian windsurfing industry in which diminished demand absorptive capacity (in the terms of the model) was a factor underlying sectoral collapse. We discuss how development of absorptive capacity of demand presents a collective action problem for an industry sector, and the role of demand-side factors as constraints in industry and innovation policy.